2017
DOI: 10.1111/1462-2920.13633
|View full text |Cite
|
Sign up to set email alerts
|

Happens in the best of subfamilies: establishment and repeated replacements of co‐obligate secondary endosymbionts within Lachninae aphids

Abstract: Virtually all aphids maintain an obligate mutualistic symbiosis with bacteria from the Buchnera genus, which produce essential nutrients for their aphid hosts. Most aphids from the Lachninae subfamily have been consistently found to house additional endosymbionts, mainly Serratia symbiotica. This apparent dependence on secondary endosymbionts was proposed to have been triggered by the loss of the riboflavin biosynthetic capability by Buchnera in the Lachninae last common ancestor. However, an integral large-sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 57 publications
3
80
0
Order By: Relevance
“…Microbes can also facilitate the establishment of other microbial species within the microbiome community. Some symbiont species are more likely to occur in coinfections; for example, Fukatsui symbiotica (Manzano-Marín, Szabó, Simon, Horn, & Latorre, 2017) is a facultative symbiont that is almost always found in coinfection with…”
Section: Interactions Within Microbial Communitiesmentioning
confidence: 99%
“…Microbes can also facilitate the establishment of other microbial species within the microbiome community. Some symbiont species are more likely to occur in coinfections; for example, Fukatsui symbiotica (Manzano-Marín, Szabó, Simon, Horn, & Latorre, 2017) is a facultative symbiont that is almost always found in coinfection with…”
Section: Interactions Within Microbial Communitiesmentioning
confidence: 99%
“…Many of these symbioses display high partner fidelity over long periods of evolutionary time, often with strict co-diversification of host and symbiont lineages [5,6]. However, both symbiont loss and symbiont switching, often to a phylogenetically distant microbial taxon, has been identified in many host lineages, especially among insects [7][8][9][10], as well as in other invertebrate taxa [11]. It has been suggested that symbiont switching may be linked to changes in host traits, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2011; Manzano-Marín and Latorre 2014; Manzano-Marín et al. 2016, 2017). Accordingly, Cinara species (Aphididae: Lachninae) have been consistently found to host an additional bacterial co-obligate symbiont, most commonly S. symbiotica (Lamelas et al.…”
Section: Introductionmentioning
confidence: 99%